SOCIALIZATION ACTIVITIES TO GET TO KNOW MORE ABOUT IMMIGRATION POLYTECHNIC BY IMMIGRATION POLYTECHNIC CADETS AT THE IMMIGRATION OFFICE CLASS I BORDER CONTROL SURAKARTA - Rizky Noor Jaya Pramuditya; Seno Setyo Pujonggo (Jurnal Abdimas Imigrasi, 2021)
Latihan Kerja Bhumi Pura (LATJAPURA) activity is a job training given to Immigration Polytechnic cadets that aim to understand the provisions, policies, and immigration regulations at the Immigration UPT directly. In LATJAPURA activity, , especially at the Immigration Office Class I TPI Surakarta, socialization activities were carried out using live Instagram media to get to know the public more closely about what an Immigration Polytechnic official school was which was explained directly by the Immigration Polytechnic cadets who did job training at the UPT. With this socialization, it is hoped that the public can know more about the official school of the Immigration Polytechnic, especially for students who want to register as cadets at the Immigration Polytechnic and know how life is in it.